Fatty acids and their carbon isotopes in two nearshore sediment cores from the coastal South China Sea - Wei, Bingbing; Mollenhauer, Gesine; Kusch, Stephanie; Hefter, Jens; Grotheer, Hendrik; Schefuß, Enno; Geibert, Walter; Ransby, Daniela; Wu, Yijing; Gentz, Torben; Bonk, Elizabeth; Jia, Guodong (PANGAEA, 2023)
This data set includes nuclide activities, grain size, content, δ¹³C and F¹⁴C of bulk OC and Fatty acids in two nearshore sediment cores collected by the piston corer from coastal South China Sea. These data could help us to constrain the anthropogenic perturbations of different terrestrial OC export to the coastal ocean.
Keywords: bulk 13C and C14 analyses; coastal South China Sea; Compound-specific 13C and 14C analyses; fatty acids; Pearl River Basin